The common law in colonial America. Volume IV, Law and the constitution on the eve of independence, 1735-1776 - Nelson, William E. (William Edward), 1940- (New York, NY : Oxford University Press, 2018)
After concluding that the mid-eighteenth-century colonial legal system usually functioned effectively, this text focuses on constitutional events leading to the American Revolution, showing how lawyers used ideology in the interests of their clients and became revolutionary leaders.
Previously issued in print: 2018.
Includes bibliographical references and index.
Specialized.
Description based on online resource; title from home page (viewed on April 18, 2018).
Keywords: Law -- United States -- History; Common law -- United States -- History; United States -- History -- Colonial period, ca. 1600-1775.; Law; Laws of specific jurisdictions & specific areas of law